Evaluation of the removal of total phosphorus from sanitary effluent by Chlorella vulgaris in a small batch photobioreactor - Pereira, Juliana Cabral; Nascimento, Amanda Isabelly Leite Figueiredo; Carvalho, Yasmin Oliveira; Silva, Cristina Ferraz (Scientia Plena, 2018)
The search of the scientific community for efficient and cheap technologies for the treatment of wastewater in Brazil continues being a challenge, mainly in the effort to encourage the government, responsible for the application and proliferation of these technologies. The release of contaminated effluent without treatment in the aquatic bodies leads to the degradation of these environments, what requires the reuse of these waters, facing environmental sustainability. In this context, microalgae establish a promising alternative, once the main attribute of algae culture in wastewater is its ability to efficiently assimilate organic carbon and inorganic nutrients from wastewater to achieve a clean effluent with efficient nutrient removal, besides a biomass production, accumulation of lipids, which can be converted into biodiesel. Assuming the important role of photosynthetic CO2 fixation, which helps to mitigate the alarming effects of the release of greenhouse gases into the atmosphere. The main objective of this work was to evaluate the capacity of the microalga Chlorela vulgaris in the removal of phosphorus from the sanitary sewage collected at the effluent treatment plant at Federal University of Sergipe using a small batch reactor. The results showed that the species Chlorella vulgaris were able to assimilate phosphorus and to remove organic matter (Chemical Oxygen Demand, COD) from the effluent. The results showed that photobioreactors using microalgae for the treatment of effluents is a promising technique and motivate additional studies, mainly due to their capability of adding value to the biomass generated during the treatment.